Prevalence and antibiotic resistance of Mycoplasma genitalium among STI clinic attendees in Western Canada: a cross-sectional analysis. Issue 7 (10th July 2017) - Gratrix, Jennifer; Plitt, Sabrina; Turnbull, LeeAnn; Smyczek, Petra; Brandley, Judith; Scarrott, Ron; Naidu, Prenilla; Parker, Penny; Blore, Brenda; Bull, Amy; Shokoples, Sandy; Bertholet, Lindsay; et al.
Abstract : Objectives: To determine the prevalence and correlates of M ycoplasma genitalium (MG) infection among men and women, determine the prevalence of gene mutations conferring resistance and compare test performance of female specimen types. Methods: A cross-sectional study was conducted on specimens collected for gonorrhoea (NG, Neisseria gonorrhoeae ) and chlamydia (CT, Chlamydia trachomatis ) among male and female Alberta STI clinic attendees using the M. genitalium transcription-mediated amplification-research use only test. Positive specimens were sequenced for 23SrRNA, parC and gyrA genes. Gender-stratified analysis compared test results using χ 2 or Fisher's exact test, Mann-Whitney U test and logistic regression. Female endocervical and urine specimens were compared. Results: A total of 2254 individuals were tested; 53.8% (n=1212) were male. Male prevalence of MG was 5.3%; CT was 5.9% and NG was 1.8%. Correlates of male infection were a non-gonococcal urethritis diagnosis and NG coinfection. MG prevalence for women was 7.2%; CT was 5.8% and NG was 1.8%. Correlates of female infection were younger age, Indigenous/Other ethnicity and CT/NG coinfection. Nearly two-thirds of eligible specimens had mutations associated with macrolide resistance and 12.2% of specimens had a parC mutation signifying possible moxifloxacin resistance. There was high concordance (98.1%) of results between urine and endocervical swabs. Conclusions: The high prevalence of MG relative to CT and NG supports the incorporation of MG testing into routine sexually transmissible infection screening. The high rate of resistance to macrolides and moxifloxacin raises concerns about treatment options. The good concordance of results between urine and endocervical swabs supports the use of female urine specimens for testing.